An integrated analysis of herpes virus infections from eight randomized clinical studies of baricitinib in adults with moderate‐to‐severe atopic dermatitis. (18th May 2022) - Werfel, T.; Irvine, A.D.; Bangert, C.; Seneschal, J.; Grond, S.; Cardillo, T.; Brinker, D.; Zhong, J.; Riedl, E.; Wollenberg, A.
Abstract: Background: Atopic dermatitis (AD) is associated with an increased risk for viral infections including those caused by herpes simplex virus and varicella zoster virus. Objectives: This study examined treatment‐emergent (TE) herpes simplex infection including eczema herpeticum (EH), and herpes zoster (HZ), in adult patients with AD receiving ≥1 dose of baricitinib (BARI), an oral selective inhibitor of Janus kinase 1/2. Methods: We evaluated data from six double‐blinded, randomized, placebo‐controlled (PC) trials and two long‐term extension studies, within three analysis sets: PC, 2–4‐mg BARI extended and All‐BARI‐AD. Frequency, incidence rate (IR)/100 person‐years (PYs) and clinical characteristics of TE‐herpes simplex, EH and HZ were reported. Results: In the All‐BARI‐AD dataset ( n = 2531; 2247 PYs), herpes simplex was reported in 8.9% of patients ( n = 224; IR = 10.3). Most herpes simplex events were rated as mild or moderate (93.3%), rarely led to permanent discontinuation (2.2%) and presented mostly as oral/perioral herpes simplex (51.3%). TE‐EH occurred at a low frequency (All‐BARI‐AD 1.7% n = 43; IR = 2.0) and were reported in 0.5%, 0.2% and 1.4% of patients receiving placebo, 2‐mg or 4‐mg BARI respectively. In the All‐BARI‐AD dataset, most events were investigator‐rated as mild/moderate (79.1%), affected ≤2% of the body surface area (74.2%) and occurred as single events (88.4%). Serious TE‐EH ( n = 11) occurred exclusively in patients with poor disease control (vIGA‐AD™ score ≥3) at infection onset. TE‐HZ was reported in 2.1% of BARI patients ( n = 53; IR = 2.3), without a dose relationship during the PC period (IR = 2.7 and IR = 0.0) or the extended dataset (IR = 3.7 and IR = 1.7) for 2‐ or 4‐mg BARI respectively. Conclusions: TE‐herpes simplex was common, while occurrence of EH was uncommon. Most events of EH were localized with involvement of a small BSA and were linked to poor disease control. Events of HZ were rare in the PC dataset and without a dose dependent increase in frequency.